Evidence that oxidative stress is higher in replacement gilts than in multiparous sows. Issue 5 (14th April 2016) - Roy, C.; Lavoie, M.; Richard, G.; Archambault, A.; Lapointe, J.
Summary: The recent success obtained in term of increasing the litter size of sows has not correlated with a reduction of replacement rate. There is thus an increased economic demand for gilts with optimal reproductive potential and longevity. Unfortunately, replacement gilts are known to be more susceptible to diseases and less productive than multiparous sows. Interestingly, reproductive performance, resistance to diseases and longevity could all be largely affected by oxidative stress. To investigate whether oxidative stress conditions could account for the poor longevity of gilts, three distinct groups of conventional Yorkshire × Landrace sows were formed based on their similar age and parity (gilts, second parity sows as well as fourth to fifth parity sows). All animals were slaughtered during the post‐ovulatory period, and blood as well as tissue samples were collected. Biomarkers of oxidative damage to proteins (carbonyls) and DNA (8‐OHdG) were analysed in samples. Specific mRNA expression of major antioxidants such as glutathione peroxidases 1, 3 and 4 ( GPx1, GPx3, GPx4 ) as well as superoxide dismutases 1 and 2 ( Sod1, Sod2 ) were monitored in liver and kidney samples by quantitative RT‐PCR. Specific enzymatic activities of both GPx and SOD were measured by spectrophotometric assays. The plasma concentration of protein carbonyls was significantly different between the three groups with the highest concentration being observed in gilts (p ≤ 0.001). The mRNA expression levels of GPx1 and GPx4 were also significantly increased in the liver of gilts when compared to multiparous sows (p ≤ 0.05). SOD2 enzymatic activity was found to be higher in the liver of gilts than multiparous sows (p ≤ 0.05). Taken together, these results indicate that replacement gilts sustain significantly higher oxidative conditions than multiparous sows. Current findings may contribute to the design of nutritional regimens that will increase the productivity of gilts by counteracting oxidative stress.